Evidence that cagA+Helicobacter pylori strains are disappearing more rapidly than cagA− strains. Issue 3 (1st March 2002) - Perez-Perez, G I; Salomaa, A; Kosunen, T U; Daverman, B; Rautelin, H; Aromaa, A; Knekt, P; Blaser, M J
Abstract : Background and aims: The prevalence of Helicobacter pylori colonisation in populations in developed country has been declining, as shown by community based serological surveys of adults in Vammala, Finland in 1973 and 1994. In this study, we determined whether the proportion of subjects colonised by cagA + or cagA − H pylori strains has changed as the overall prevalence of H pylori + has declined. Methods: We examined 911 sera from Vammala's study for antibodies to the CagA antigen of H pylori using a truncated CagA protein as the antigen in an ELISA and we examined the trend in acquisition and carriage of cagA + strains. Results: As expected, the prevalence of carriage of both cagA + and cagA − strains fell between 1973 and 1994 (p<0.001). However, the prevalence of cagA + strains among those <45 years declined (34% to 8%) significantly (p<0.001) more than for cagA − strains (12% to 6%). Of 221 subjects with paired serum samples, 12 (5.4%) changed H pylori status; the estimated seroconversion and reversion rates were 0.4% and 0.13% per year, respectively. Except for the few individuals who changed serostatus, absolute antibody levels to H pylori antigens, including CagA, changed little over the 21 year period. Conclusions: The decline in CagA seroprevalence predominantly reflects declining acquisition of cag + strains in younger subjects. In addition, these data confirm that H pylori acquisition chiefly occurs during childhood but continues to occur during adulthood, albeit at low rates, in developed countries.